(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Physical fitness tests play a crucial role in evaluating the physical capabilities of students. This article explores the importance of such tests in determining students’ fitness levels and overall health. It discusses the necessity of integrating fitness assessments into educational systems to promote healthier lifestyles and enhance academic performance.